Feedback Environment sebagai Prediktor Psychological Well-Being Generasi Z di PT Altrak 1978 Karang Joang - Winner Agape Krisetya; Sutarto Wijono (Journal of Innovation Research and Knowledge, 2026)
Psychological well-being is an important aspect of employees' functioning in the workplace, particularly among Generation Z employees who are adapting to changing work demands and organizational environments. One workplace factor that may be associated with psychological well-being is the feedback environment, which reflects employees' perceptions of feedback received through interactions with supervisors and coworkers. This study aims to examine feedback environment as a predictor of psychological well-being among Generation Z employees at PT Altrak 1978 Karang Joang. The study employed a quantitative approach with a correlational design. Participants were 108 Generation Z employees selected using purposive sampling. Data were collected using the short version of the Feedback Environment Scale (FES) adapted from Louro and Gabardo-Martins (2024) and the Psychological Well-Being Scale adapted in the Indonesian context by Humaidah and Mulyono (2025). Data were analyzed using simple linear regression with the assistance of SPSS version 26. The results showed that feedback environment significantly predicted psychological well-being (p = .019). The correlation coefficient was R = .226, indicating a weak relationship, while the coefficient of determination was R² = .051, indicating that feedback environment explained 5.1% of the variance in psychological well-being. These findings indicate that feedback environment is one workplace factor associated with psychological well-being among Generation Z employees, although other factors also contribute to psychological well-being.